2001
DOI: 10.1016/s0925-4773(01)00414-2
|View full text |Cite
|
Sign up to set email alerts
|

Shh and Ptc are associated with taste bud maintenance in the adult mouse

Abstract: In mammals, taste receptor cells are organized into taste buds on tongue. Taste buds are trophically maintained by taste neurons and under continuous renewal, even in adults. We found that the receptor for Sonic hedgehog (Shh), Patched1 (Ptc), was expressed around taste buds where cells were proliferating, and that Shh was expressed within basal cells of taste buds. Denervation caused the loss of Shh and Ptc expression before the degeneration of taste buds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 10 publications
2
77
0
Order By: Relevance
“…2F and Fig. S3A), as also noted by others (21)(22)(23)(24). Note that the mG marking of Shh-expressing cells within the taste bud is driven by the CAG promoter inserted at the R26 locus.…”
Section: Significancesupporting
confidence: 79%
“…2F and Fig. S3A), as also noted by others (21)(22)(23)(24). Note that the mG marking of Shh-expressing cells within the taste bud is driven by the CAG promoter inserted at the R26 locus.…”
Section: Significancesupporting
confidence: 79%
“…[25][26][27] It has previously been reported that the Shh pathway is active also in the adult mouse tongue, suggesting a role in tongue epithelial/taste bud maintenance. 28 Together these findings suggest that in the adult tongue Wnt/␤-catenin is upstream of Shh and that Shh negatively regulates Wnt signaling in tongue epithelial/taste bud maintenance.…”
Section: Discussionmentioning
confidence: 87%
“…Our double-staining experiments for BMP4-ß-gal and proliferation markers revealed that the BMP4-expressing cells in the subepithelial lamina propria are also mitotically inactive, suggesting that in concert, these epithelial and mesenchymal BMP4 cells adjacent to taste buds may maintain the niche, or signaling center for taste bud stem cells. Interestingly, Miura [32] report that Shh is expressed exclusively in basal cells within taste buds, whereas Ptch1 , a Shh receptor (reviewed by Ingham and McMahon, 2001) [75], is expressed in the epithelial cells outside of taste buds, but adjacent to intragemmal Shh expressing cells. Moreover, mitotic cells, as detected via short term BrdU incorporation are mainly in the Ptch1 expressing region, raising the likelihood that Ptch1 expressing cells comprise the transit amplifying population, and possibly the taste bud stem cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sonic hedgehog ( Shh ) is expressed in basal cells (type IV) within taste buds, while the Shh receptor, Patched1 ( Ptch1 ), is expressed in perigemmal epithelial cells adjacent to Shh -expressing cells [32,33]. Mash1 , a transcription factor in the Notch pathway, is expressed in a subset of differentiated type III cells, and is also expressed in a subset of Shh expressing basal cells, suggesting a possible function for Mash1 in the transition from basal cells to type III cells [29,34].…”
Section: Introductionmentioning
confidence: 99%